Assessing the market value effects of intellectual capital disclosure: insights from New Zealand - Abdolzahraei, Zeinab; Cheah, Jun Hwa; Choo, Wei Chong; Abdullah, Abdul Rashid (Inderscience Publishers, 2024)
This study investigates the impact of intellectual capital disclosure on the market value of listed firms in New Zealand from 2016 to 2018, using a stakeholder theory perspective. Given modern investors’ heightened interest in firms’ intellectual aspects, empirical exploration is imperative. Employing content analysis to assess intellectual capital disclosure levels and multiple regression for measuring impact, our research is based on a sample of 114 observations across 38 firms. Empirical findings affirm a strong positive correlation between intellectual capital disclosure and market value for New Zealand-listed firms during the study period. Notably, every element of intellectual capital disclosure contributes positively to market value, with human capital disclosure exhibiting the most significant influence, despite being the least reported component. These results align with stakeholder theory, emphasising the pivotal role of disclosure in influencing stakeholder decisions, particularly among investors. Our study systematically assesses each disclosure component’s effect on market value and empirically tests intellectual capital disclosure’s impact in New Zealand’s developed economy. Copyright © 2024 Inderscience Enterprises Ltd.